Implementasi Corporate Social Responsibility Berdasarkan Tri Hita Karana pada Lembaga Perkreditan Desa Kesiman Denpasar Timur - Krisnaningrum, Ni Putu Anggie; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 31 No 7 (2021)DO - 10.24843/EJA.2021.v31.i07.p17, 2021)
The Village Credit Institution as a financial institution runs its business emphasizing the Tri Hita Karana concept. Based on this concept, LPD has Corporate Social Responsibility to the surrounding community. This study used a qualitative approach in the form of a descriptive ethnographic method. The informants in this study were treasurers, staff, and customers. Data collection was carried out by interview and documentation. The results show that CSR implementation from the Parhayangan aspect is realized by performing the yajnya, contributing to villages or communities that are carrying out religious ceremonies, and conducting funds, from the Pawongan aspect manifested by providing assistance to residents affected by disaster and who are grieving in the form of cash and from the Palemahan aspect it is manifested by maintaining cleanliness and help each other. Keywords: Corporate Social Responsibility; Tri Hita Karana; Village Credit Institution.